Candidate halophytic grasses for addressing land degradation: Shoot responses of Sporobolus airoides and Paspalum vaginatum to weekly increasing NaCl concentration. Issue 2 (3rd April 2017) - Pessarakli, Mohammad; Breshears, David D.; Walworth, James; Field, Jason P.; Law, Darin J.
ABSTRACT: In many arid and semiarid regions worldwide, high levels of soil salinity is a key driver of land degradation, as well as a key impediment to re-establishing plant cover. Combating land degradation and erosion associated with soil salinity requires experimental determination of plant species that can grow in soils with high levels of salinity and can be used to re-establish plant cover. Herein, we evaluated the responses of untested candidate cultivars of two halophytic grass species to high soil salinity: alkali sacaton ( Sporobolus airoides Torr.) and seashore paspalum ( Paspalum vaginatum Swartz). We evaluated the growth responses of both species in a greenhouse under control (no-salt) and various levels of NaCl salinity (EC 8, 16, 24, 32, 40, and 48 dSm −1 ) using Hoagland solution in a hydroponics system in a randomized complete block design trial. At all salinity levels, sacaton grass had a greater shoot height, shorter root length, lower shoot fresh and dry weights, and poorer color and general quality compared to seashore paspalum. The shoot fresh and dry weights of both grasses were greatest at the low to medium levels of salinity, with the greatest response observed at EC 16 dSm −1 . At the highest level, salinity significantly reduced shoot fresh and dry weights of both grasses. Because growth of both halophytic species exhibited high tolerance to salinity stress and were stimulated under low to medium levels of salinity, both species could be considered suitable candidates for re-establishing plant cover in drylands to combat desertification and land degradation associated with high levels of soil salinity.